Thyroid Function Status of Female Nurses Working Night-shift at a Tertiary Care Hospital (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Night shift work has well-known adverse effects on health like sleep disturbances and other medical conditions including thyroid diseases. Various studies have revealed that the effect of night shift work on healthis mainly related to its interference with circadian rhythm, which can also influence thyroid hormone levels in accordance with sleep patterns. Therefore, night work can modify thyroid function and increase the risk of thyroid disorders. The present study was therefore conducted to evaluate the impact of the night shift work on the thyroid function status of female nurses in a tertiary care hospital.Methods: This case-control study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka over a period of 1 year from January 2021 to December 2021. All female nurses (in the age range of 25-50 years) working at Dhaka Medical College in different shifts were the study population. Of them, the case group consisted of 90 female nurses who worked the night shift in different wards from 8.00 pm. to 8.00 am and the control group consisted of 90female nurses who worked the morning shift in the Outpatient Department (OPD) from 8.00 am to 2.00 pm. However, nurses with a personal or family history of sleep disorder, taking medications that may interfere with sleep, history of diabetes mellitus, bronchial asthma, or diagnosed with any kind of thyroid disease, such as Hashimoto’s thyroiditis, and pregnant nurses were excluded from the study. While the exposure variable was shift-work, the outcome variable was thyroid function status, evaluated in terms of serum FT4, FT3, and TSH and the presence of thyroid disorders.Results: The cases and controls were almost alike in terms of age, BMI, and blood pressure. The mean age of the case and the control groups were between 34 and 35 years with no significant difference between the groups. While serum levels of free thyroxine (FT4) and free triiodothyronine (FT3) were somewhat reduced in the case group than those in the control group, the serum TSH was significantly elevated in the former group than that in the latter group – a picture typical of subclinical hypothyroidism. Overt hypothyroidism was also higher in the former group than that in the latter group. Subclinical and clinical hyperthyroidism was found in 2(2.2%) and 3(3.3%) subjects of the control group only. Overall, 60% of the cases had some form of thyroid disorders as opposed to 15% of the controls with the risk of having thyroid disorders in night shift nurses being > 8(95% CI = 4.1 – 17.5) times higher than that in morning shift nurses(p < 0.001).Conclusions: The study concluded that night shift nurses may have a higher risk of developing subclinical hypothyroidism due to significantly higher levels of TSH and normal FT3, and FT4 levels. About two-fifths of the nurses working night shifts are at increased risk of having thyroid disorders, primarily subclinical hypothyroidism.Ibrahim Card Med J 2022; 12 (2): 40-45